Horticulture for a greener world - Hubbard, L. Ron (La Fayette Ron) 1911-1986 (RON : the L. Ron Hubbard series, 2012)
"In this very special story of transcendent revelations and global repercussions, track the course of L. Ron Hubbard's horticultural discoveries. Told through articles and personal notes--here is a journey of discovery bearing upon all living things and the very essence of life itself."--